A pluralidade humana como condição da política em Hannah Arendt - Alencar, Dariôhana Moreira (2017)
The objective of this study is to interpret the term human plurality according to the politics philosophy of Hannah Arendt. The concept of politics, in consonance with her mind, can be understood as a gap among human beings while plurality is seen as a condition for these politics to exist. Connections with the sense of action and discourse have been studied in order for a better understanding of such concepts as they guarantee human plurality and freedom. Regarding this guarantee, the author exposes the neglect about the previously mentioned political gap, the public space. This neglect is shown, just as in the traditional political thought, as the replacement of action by contemplation, and action has been associated to violence. This can be especially seen in the totalitarian phenomenon emergence. In the light of this phenomenon, Arendt asks if politics still makes any sense; in other words, what remains after a system of which principle is the denial of the man? To answer this question, we appeal to the aspect of human plurality that shelters our most fundamental capacities, namely, action and discourse. These capacities show a way to escape the obscuring politics and ensure a place that accommodates the human being in all aspects. This essay tries to bring back the sense of politics and asks for the pertinence of the author's thought nowadays.